The model for evaluation of corporate strategic changes in the context of climate change: plywood manufacture - Tamošiūnas, Andrius (Journal of Business Economics and Management, 2014)
The paper presents the model for evaluation of corporate management measures aimed at solving tasks related to climate change challenges (UN 1998; EP 2009; EC 2013) faced by enterprises and inevitably leading to corporate strategic changes. In a detailed yet concise manner, the paper analyses the model for evaluation of corporate strategic changes and specifies techniques for its application focusing on the following proposed criteria: the market share; financial capacity; business development potential; product competitiveness; and productivity. The paper reveals the benefit of the use of the proposed model for corporate strategic changes. Greater possibilities are created to rationalise the process of corporate strategic changes and the use as well as development of human, material and financial potentials, which lead to greater competitiveness of an enterprise. The model guides to directions and actions to be taken in order to continue increasing effectiveness of an enterprise in the context of climate change objectives. The evaluation model suggested by the author is also analysed according to flexibility of proposed techniques, the characteristics of which can be modified and adjusted depending on specifics of the changing business environment. This allows ensuring and promoting competitiveness of an enterprise while pursuing the climate change challenges (UN 1998; EP 2009; EC 2013) set for businesses. First published online: 08 Jul 2013